A Cooperative-Based Village-Owned Enterprise (BUMDes) Governance Model to Achieve Sustainable Development Goals (SDGs) - Catur Prabowo; Ig. Henri Pelupessy; Adi Saputra (Universitas Negeri Semarang, 2025)
This study aims to develop a cooperative-based governance model for Village-Owned Enterprises (BUMDes) to support the achievement of the Sustainable Development Goals (SDGs). The research was conducted at BUMDes Sinar Mandiri Batursari Sakti using a participatory qualitative approach through literature reviews, field observations, in-depth interviews, Focus Group Discussions (FGDs), and a pilot implementation of the governance model. The findings reveal that the application of cooperative principles in BUMDes governance enhances institutional legitimacy, strengthens accountability, and promotes broader community participation. The integration of cooperative values also reduces elite domination, reinforces community ownership, and expands the village’s socio-economic impact. Furthermore, the governance model aligns with the achievement of several SDGs, particularly poverty reduction (SDG 1), decent work and economic growth (SDG 8), reduced inequalities (SDG 10), and partnerships for the goals (SDG 17). Therefore, the proposed cooperative-based governance model is not only relevant for improving the performance of BUMDes Sinar Mandiri Batursari Sakti but also has strong potential to be replicated in other BUMDes with adjustments to local contexts.